2017
DOI: 10.1192/bjp.bp.117.198754
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive mood dysregulation disorder in offspring of parents with depression and bipolar disorder

Abstract: It has been suggested that offspring of parents with bipolar disorder are at increased risk for disruptive mood dysregulation disorder (DMDD), but the specificity of this association has not been established.We examined the specificity of DMDD to family history by comparing offspring of parents with (a) bipolar disorder, (b) major depressive disorder and (c) a control group with no mood disorders.We established lifetime diagnosis of DMDD using the Schedule for Affective Disorders and Schizophrenia for School A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Parents of youth with narrowly defined BD were significantly more likely to have BD (14/42, 33.3%) than parents of youth with SMD (1/37, 2.7%; Brotman et al., ). Indeed, a recent study found higher rates of DMDD symptoms in offspring of parents with depression than offspring of parents with BD, and DMDD diagnoses were only present in the former (Propper et al., ). Third, behavioral and functional MRI studies have found that while both youths with BD and those with SMD have impairments in labeling facial emotions (Guyer et al., ; Rich et al., ), the neural correlates of this deficit differ between the two groups (Brotman et al., ; Thomas et al., ; Wiggins et al., ).…”
Section: Disruptive Mood Dysregulation Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Parents of youth with narrowly defined BD were significantly more likely to have BD (14/42, 33.3%) than parents of youth with SMD (1/37, 2.7%; Brotman et al., ). Indeed, a recent study found higher rates of DMDD symptoms in offspring of parents with depression than offspring of parents with BD, and DMDD diagnoses were only present in the former (Propper et al., ). Third, behavioral and functional MRI studies have found that while both youths with BD and those with SMD have impairments in labeling facial emotions (Guyer et al., ; Rich et al., ), the neural correlates of this deficit differ between the two groups (Brotman et al., ; Thomas et al., ; Wiggins et al., ).…”
Section: Disruptive Mood Dysregulation Disordermentioning
confidence: 99%
“…However, the prevalence of DMDD in epidemiological studies suggests that this was an exaggerated concern; DMDD is relatively rare with a prevalence around 1% and it appears to capture children with severe impairment, rather than the typically developing majority (Copeland et al., ). Actually, DMDD prevalence is low (3.3%) even in youth at risk for mood disorders (Propper et al., ).…”
Section: Disruptive Mood Dysregulation Disordermentioning
confidence: 99%
“…[ 30 ] One unique finding to this study is that children who presented with behavioral disturbances which do not account for any diagnoses also had family history of mental disorders. Studies done by Sparks et al .,[ 23 ] Propper et al .,[ 31 ] and Dougherty et al . [ 32 ] reported that family history of mood or substance disorder is a strong predictor of DMDD; in this study, we also found that majority of children with DMDD had family history of ADS, depression, and bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Öfke patlamaları ve irritabilite gibi YDDB semptomları, MDB olan ebeveynlerin çocuklarında en sık görülen semptomlar arasındadır. 10 Ebeveynlerinde depresyon öyküsü olan çocukların irritabilite açısından risk teşkil ettiği bildirilmektedir. 8 13 tarafından yapılmıştır.…”
Section: Introductionunclassified